Aging and Proteins: What Does Proteostasis Have to Do with Age? - Magalhaes, S.; Goodfellow, B.J.; Nunes, A. (Current Molecular Medicine, 2018)
The world is aging and we must face the challenges that this brings. One of the reasons for the increasing aging of the world's population is the increase in life expectancy and, since we live longer, it is of paramount importance to live well and to prevent age-associated diseases. In this way, it is crucial to improve knowledge of the aging process and of the mechanisms that contribute to it. Ideally it would be of great interest to have a panel of biomarkers of healthy aging that would allow an estimate of the biological age of an individual. One of the changes that greatly contribute to aging is the loss of protein homeostasis, also called proteostasis. To ensure the proper function of cells and to maintain cellular proteostasis, organisms have developed systems to control protein synthesis, folding and degradation. Loss or dysfunction of proteostasis is at the root of many well-studied human neurological diseases, such as Alzheimer's disease and, more recently, it has been implicated in the aging process with some reports showing long-lived animals to have improved proteostasis. Growing evidence suggests a strong link between modifications in the quantity and/or activity of several players involved in proteostasis and longevity. In this review, we give an overview of the main characteristics of aging with focus on proteostasis. We present how changes in components of proteostasis, during aging, impact the lifespan of model organisms. We also briefly review the current state of aging biomarkers and discuss the potential of proteostasis network components as markers of healthy aging.
Keywords: proteostasis